The role of university students in protecting the environment - Hassan, Najmaldin Ezaldin (Universitas Pakuan, 2024)
The global environmental crisis, characterized by challenges such as climate change, deforestation, pollution, and biodiversity loss, requires urgent action. As an educated and socially aware demographic, university students are uniquely positioned to contribute significantly to environmental protection and sustainability. This paper explores the multifaceted role of university students in addressing environmental issues through education, advocacy, research, and sustainable campus initiatives. It highlights how student-led movements, such as Fridays for Future, have propelled environmental awareness into public discourse and influenced institutional and policy changes. Students' involvement in research and innovation, particularly in renewable energy, sustainable agriculture, and waste management, has led to groundbreaking solutions to mitigate environmental degradation. On university campuses, students drive sustainability through initiatives to reduce waste, conserve energy, and promote biodiversity. Their advocacy extends beyond campuses to regional, national, and international platforms, where they actively shape environmental policies and push for ambitious climate action. Despite challenges such as limited funding and institutional resistance, university students continue to overcome barriers by leveraging academic resources and collaborating with external organizations. Ultimately, university students play a pivotal role in fostering long-term environmental stewardship and promoting sustainable development at both local and global levels.